Ultrastructural changes caused by Datura innoxia seeds extract in the liver of rats - Valiyeva, A. K.; Garayev, E. A.; Gasimov, E. K.; Rzayev, F. H.; Jafarova, R. A. (Regulatory Mechanisms in Biosystems, 2024)
The main purpose of the investigation is to determine the toxic effects of the alkaloid-rich extract of the seeds of Datura innoxia Mill. on the liver tissue of white laboratory rats. Datura innoxia is an annual herb belonging to the Solanaceae family and widely distributed in the territory of the Republic of Azerbaijan. Datura species are known as a source of tropane alkaloids, which have toxic and therapeutic effects. The primary symptoms of Datura poisoning, related to the anticholinergic effects of tropane alkaloids, include hallucinations, mydriasis, dry skin, dizziness, tachycardia, reduced urinary retention, etc. The various pathological changes in living organisms due to the toxicity of tropane alkaloids were detected by different groups of researchers. In the presented study alkaloid-rich extract of the plant seeds was prepared using the acid-base extraction method and dissolved in 0.9% physiological saline. Animals were subjected to oral administration of the alkaloid-rich extract for a period of 30 days at a dose of 5 mg/kg body weight, once daily. At the end of experimental study, liver samples were obtained from control and experimental groups. Araldite-Epon blocks were prepared following established protocols for electron microscopy, semi-thin and ultrathin sections were obtained using a Leica EM UC7 ultramicrotome. The sections were stained and examined under Primo Star light microscope and JEM-1400 transmission electron microscope (TEM). The results revealed increased vascular permeability due to damage to the endothelial cells of the central veins and sinusoids. Edema formation was observed in the periendothelial and perivascular spaces. Stagnation in the sinusoidal lumen and the presence of bridge-like connections among the majority of sinusoids were identified. Necrosis was observed in the perivascular spaces of veins. The membranes of hepatocytes, which constitute the parenchyma of the liver, were damaged, and cytoplasmic organelles migrated to the intercellular and Disse spaces. Glycogen in the cytoplasm of hepatocytes transformed into an amorphous form, with certain nuclei of hepatocytes experiencing dystrophy, the tight junction of the bile canaliculus was disrupted, and sometimes not visible. The identified pathological changes indicate that the utilization of the alkaloid-rich extract at a dose of 5 mg/kg over 30 days resulted in toxic effects on the white laboratory rats.